2008
DOI: 10.1016/j.jtcvs.2007.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for interstage death after stage 1 reconstruction of hypoplastic left heart syndrome and variants

Abstract: The presence of intact atrial septum and older age at the time of surgery are associated with a higher risk of interstage death. In addition, postoperative arrhythmia and airway complications are associated with a higher risk of interstage death in univariate analysis. The results of this study provide a focus for interstage monitoring and risk stratification of these high-risk infants, which may improve overall survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
181
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(191 citation statements)
references
References 33 publications
7
181
3
Order By: Relevance
“…22 It has been shown, however, that there are subgroups of patients within the spectrum of HLHS which have poorer outcomes when treated by traditional surgical palliation. 10,23 Also, the classical staged palliation approach appears to have reached a stagnation point, 24 no further improvements being possible with the currently available technology, with recent cumulative early and interstage mortality of 5%---30% for standard-risk patients 25---27 but as high as 30%---50% in high-risk patients. 11,12 A recent Pediatric Heart Network-sponsored multicenter randomized trial compared the Norwood procedure with a modified BT shunt versus the Sano modification, 26 with the primary endpoint of death or transplantation at one year and the secondary endpoints of hospital course, RV function by echo, pulmonary artery size by angiography, unintended cardiovascular interventions, and serious adverse events and complications.…”
Section: Discussionmentioning
confidence: 99%
“…22 It has been shown, however, that there are subgroups of patients within the spectrum of HLHS which have poorer outcomes when treated by traditional surgical palliation. 10,23 Also, the classical staged palliation approach appears to have reached a stagnation point, 24 no further improvements being possible with the currently available technology, with recent cumulative early and interstage mortality of 5%---30% for standard-risk patients 25---27 but as high as 30%---50% in high-risk patients. 11,12 A recent Pediatric Heart Network-sponsored multicenter randomized trial compared the Norwood procedure with a modified BT shunt versus the Sano modification, 26 with the primary endpoint of death or transplantation at one year and the secondary endpoints of hospital course, RV function by echo, pulmonary artery size by angiography, unintended cardiovascular interventions, and serious adverse events and complications.…”
Section: Discussionmentioning
confidence: 99%
“…In a single center series of 138 infants with HLHS, freedom from death or heart transplant was significantly reduced in patients who develop ventricular dysfunction in the early post-operative period after the first stage surgery both at 3 months (47 % vs. 84 %, p<0.001) and 6 months (27 % vs. 73 %, p< 0.001) (Chetan et al 2013). In a cohort study comparing 22 HLHS patients with persistent HLHS patients who experienced interstage deaths compared to 99 HLHS controls (Hehir et al 2008) and showed that the incidence of ventricular dysfunction did not differ between the two groups.…”
Section: Ventricular Dysfunction Association With Mortalitymentioning
confidence: 99%
“…A few other studies have also examined interstage death, deaths that occur between being discharged to home post-Norwood procedure and admission for the stage II procedure, and reported an incidence of two to 20 % (Rudd et al 2014;Hehir et al 2008;Furck et al 2010;Ghanayem et al 2012;Simsic et al 2004). The Milwaukee group has reported an excellent interstage survival outcome of 98 % for interstage survival using their multidisciplinary home monitoring system (Rudd et al 2014) while other groups are still reporting significant interstage mortality (Furck et al 2010;Simsic et al 2004).…”
Section: Interstage Mortalitymentioning
confidence: 99%
See 1 more Smart Citation
“…The review included eight retrospective reviews of surgical cases, [23][24][25][26][27][28][29][30] four retrospective cohort studies, [31][32][33][34] two case-control studies 35,36 and one randomised controlled trial that was reported in two papers. 26,37 Only three studies 29,36,37 included a prospective element.…”
Section: Study Selectionmentioning
confidence: 99%